Preventive measures for infections in cholecystectomies: strategies and brazilian evidence - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
Cholecystectomy, a surgical procedure performed to remove the gallbladder, is an intervention of great relevance in medical practice, and is often indicated for the treatment of biliary diseases, such as cholelithiasis and cholecystitis. In the Brazilian context, where the prevalence of these diseases is significant, cholecystectomy plays a fundamental role in the therapeutic approach.